Mechanical properties and multi-field ferroelastic response of Nb/Mn Co-doped CaBi4Ti4O15 high-temperature ferroelectric ceramics - Xu, Jiageng; Xie, Shaoxiong; Liu, Yongjie; zhou, Xiandong; Wang, Qingyuan; Zhu, Jianguo (Ceramics International, 2024)
CaBi4Ti4O15 (CBT) ceramics are promising piezoelectric materials that have been widely studied for high-temperature applications. Despite significant advancements in the electrical performance of CBT ceramics, the understanding of their mechanical behaviors remains limited, which is unfavorable for designing ceramics with high stability and reliability during high-temperature service. This work investigated the mechanical properties and fracture behaviors of Nb/Mn co-doped CaBi4Ti4O15 (CBTNM) with various doping levels, focusing on stress-strain responses and ferroelastic deformation behaviors under uniaxial compression and multi-field coupling conditions. HRTEM analysis reveals small-scale layered domain wall structures on the surface of plate-like grains. The fracture and compressive strengths of CBTNM ceramics initially decrease and then increase with an increase in doping content, and the underlying mechanisms are related to grain size, defects, and densification. CBTNM ceramics exhibit nonlinear stress-strain responses due to ferroelastic deformation under compressive loading, and the resultant irreversible domain switching strain increases with an increase in doping content, while poling can further increase the residual strain. Under multi-field loading conditions, CBTNM ceramics undergo more ferroelastic deformation events and exhibit larger residual strain. The micro-cracks, pores, complicated fracture modes, and degraded fracture surfaces with fragmental and rough features are mainly responsible for the lower elastic modulus and inferior mechanical response. This work enhances our understanding of the mechanical behaviors of high-temperature piezoelectric ceramics and provides guidance for designing high-performance piezoelectric materials for complex environmental applications.
CRIS-Team Scopus Importer:2024-10-11
Keywords: CBT-Based ceramics; Doping and poling effect; Ferroelastic deformation; Mechanical properties; Multi-field coupling